2007
DOI: 10.1200/jco.2007.25.18_suppl.9074
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of bisphosphonate associated osteonecrosis of the jaws

Abstract: 9074 Background: Intravenous bisphosphonate therapy has been used for treatment of various benign and malignant bone diseases, including bony metastasis. Recent single case reports have described osteonecrosis (ON) of the mandible or maxilla as a previously unknown complication of this therapy. Methods: Records of 638 patients treated with intravenous pamidronate or zoledronic acid were reviewed to determine the incidence of jaw ON. Number of infusions, dosing interval, dosage administered, and duration of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Several descriptive studies of BRONJ have been published in the United States [9,10], Asia [11] and Europe [12][13][14]. In addition to these studies, which were based on hospital medical records, pharmacovigilance databases have also been used to investigate BRONJ in Europe [15] and in the United States [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several descriptive studies of BRONJ have been published in the United States [9,10], Asia [11] and Europe [12][13][14]. In addition to these studies, which were based on hospital medical records, pharmacovigilance databases have also been used to investigate BRONJ in Europe [15] and in the United States [16].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Other authors have reported incidence in a similar manner. (3,4) When the published data are available as cases per person-years, they have been reported in this manner. (5,6) Of note, the Canadian survey of oral surgeons estimated the incidence of BP-associated ONJ to be 1.04 per 100,000 over a 3-year period.…”
mentioning
confidence: 99%
“…BON hastalarında tedavi planı, ağrının giderilmesini, yumuşak ve sert dokuda oluşan enfeksiyonun kontrolünü ve hastalığın ilerlemesinin engellenmesini hedefler. Bisfosfonat kullanan hastaların tedavi planını oluşturabilmek için öncelikle hastalığın şiddetini ve önerilen etkili tedavi planını belirlemeliyiz 28,31,37 (Tablo 2).…”
Section: Bisfosfonat Kullanımına Bağlı Olarak çEne Kemiklerinde Gelişen Osteonekroz Tedavisi Ve Koruyucu öNlemlerunclassified